Application of quasiconformal mapping methods to the investigation of the explosive processes impact on the environment (Моделювання, керування та інформаційні технології, 2019)
The mathematical models used to study explosive processes are given. A class of problems investigating the influence of explosive processes on the environment by the quasiconformal mappings numerical methods are outlined and their practical application are described